ANALISIS MUTU DAN KRITERIA KELAYAKAN DOKUMEN AMDAL DI KABUPATEN BOGOR DAN KOTA BOGOR - Rachma Venita; Hefni Effendi; Hari Wijayanto (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2015)
The rapid development activities that occurred in Indonesia has the potential to put pressure on the environment. It therefore requires sustainable development efforts with one instrument is Environmental Impact Assessment (EIA). Along with the development and adjustment of environmental conditions, EIA policy has undergone several changes. With EIA policy changes, evaluation on EIA performance needs to be done. The performance evaluation conducted on 15 EIA documents EIA document issued by the District and City of Bogor in 2012 through 2014. The analytical method used is the analysis of the quality of the test quality criteria document and focused on quality test aspects of consistency, necessity and relevance, feasibility analysis with weighting criteria, Pearson correlation analysis of the two respondents certified appraiser to see the similarity assessment method. From the analysis it can be seen that the quality of the documents are best seen from the EIA documents to categories of tourist accommodation facilities with a score of 81 and the analysis of the eligibility criteria resulted that three documents are not worth the environment seen from discussion of the feasibility of the benchmarks in the EIA document, also PerMenLH 08 of 2013 carried out by equally from both respondents with a positive correlation results 0.681. Keywords: quality document, eligibility criteria, Bogor, Environment Impact Assesment (EIA)